2018
DOI: 10.1038/s41467-018-04188-7
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cells can differentiate into restricted myeloid progenitors before cell division in mice

Abstract: Hematopoietic stem cells (HSCs) continuously replenish all blood cell types through a series of differentiation steps and repeated cell divisions that involve the generation of lineage-committed progenitors. However, whether cell division in HSCs precedes differentiation is unclear. To this end, we used an HSC cell-tracing approach and Ki67RFP knock-in mice, in a non-conditioned transplantation model, to assess divisional history, cell cycle progression, and differentiation of adult HSCs. Our results reveal th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 55 publications
9
55
0
Order By: Relevance
“…For all three sorted ancestor cell types, we found that addition of IL-3 and IL-6 led to a statistically significant increase in proliferation ( Figure 2C), as previously described [28,29]. Exploring the relationship between division and differentiation, in the culture without IL3 and IL6, the proportion of undivided ancestors that differentiated were 36.5% from SLAM-HSCs, 61.1% from ST-HSCs, and 35.6% from MPPs ( Figure 2D), which was in agreement with previous reports [9,10]. The addition of IL3 and IL6 didn't drastically change those values: 36.8% from SLAM-HSCs, 56.3% from ST-HSCs, and 44.8% from MPPs.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…For all three sorted ancestor cell types, we found that addition of IL-3 and IL-6 led to a statistically significant increase in proliferation ( Figure 2C), as previously described [28,29]. Exploring the relationship between division and differentiation, in the culture without IL3 and IL6, the proportion of undivided ancestors that differentiated were 36.5% from SLAM-HSCs, 61.1% from ST-HSCs, and 35.6% from MPPs ( Figure 2D), which was in agreement with previous reports [9,10]. The addition of IL3 and IL6 didn't drastically change those values: 36.8% from SLAM-HSCs, 56.3% from ST-HSCs, and 44.8% from MPPs.…”
Section: Resultssupporting
confidence: 92%
“…The addition of IL3 and IL6 didn't drastically change those values: 36.8% from SLAM-HSCs, 56.3% from ST-HSCs, and 44.8% from MPPs. SLAM-HSCs preferentially differentiated without dividing into SLAM + MEP, as reported previously [10]. On comparing the surface marker expression of differentiated and not-differentiated nondivided cells ( Figure S1B), Sca-1 high SLAM-HSCs were more likely not to differentiate, in agreement with a previous report [30].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, it has been suggested that, in some cases, cell differentiation can occur in the absence of cell division (Grinenko et al, 2018;Roch et al, 2015). Chromatin immunoprecipitation of PRC1-PRC2 proteins would be particularly informative in such cases to determine whether non-dividing, differentiating cells lose PRC1-PRC2 genomic binding or whether they use another mechanism (e.g., upregulation of pioneer TFs) to overcome PcG-TrxG antagonism and partially ''forget'' their identity on their way to a new fate.…”
Section: Cell Stem Cellmentioning
confidence: 99%
“…Intriguingly, many tissues, including the brain, skin, and hematopoietic system, feature transit-amplifying cells as intermediates between the stem and differentiated cell populations. Further, a recent study suggested that myeloid and megakaryocyte progenitors, in contrast to other blood progenitor cells, do not undergo cell division, indicating that the myeloid cells and megakaryocytes would be selected for during times of decreased progenitor proliferation 29 . Thus, proliferating non-stem progenitors may broadly serve as a buffer that enables coordinated tissue responses to a changing microenvironment while insulating the stem cell population from extreme changes.…”
Section: Discussionmentioning
confidence: 99%